Wetting behavior of selective laser melted (SLM) bio-medical grade stainless steel 316L. (2022) - Dwivedi, Suryank; Rai Dixit, Amit; Kumar Das, Alok
Abstract: Improvement in the surface wettability of the additively manufactured 316L stainless steel (316L SS) is still a challenging factor for the permanent implant's materials. The present study utilizes a laser-based additive manufacturing method, the selective laser melting (SLM) technique, to fabricate the biomedical grade stainless steel 316L (316L SS) sample. The microstructural, mechanical, and wetting behavior of the SLM sample are studied and compared with the conventionally casted 316L SS. sample. The SEM and 3D images present the top surface morphology of the fabricated parts at different magnifications. SEM micrographs show that the sample is formed bi-directionally in a 67° rot scan with the balling effects. The mechanical property of the selective laser melted and conventionally casted 316L SS is evaluated using the Vickers micro-hardness measurement. The average value of micro-hardness is 291.0147 and 186.3013HV for fabricated and casted 316L SS samples, respectively. Furthermore, the effects of balling phenomena on the surface wettability are analyzed by the sessile drop method using deionized (DI) water and Hank's balanced salt solution (HBSS), which simulates the human body fluid. Selective laser melted samples and casted 316L stainless steel sample present the contact angle values in the range of 59.3–86.9°. Selective laser melted samples show more hydrophilic wetting behavior and present a high affinity for the HBSS. Obtained results indicate that the SLM technique is a promising approach to fabricate 316L SS implants with enhanced mechanical and wetting properties.